The Canadian Sledge Dogs of the Eastern and Western Arctic - Hadwen, S. (Polar Record, 1937)
In reading of Arctic exploration one is struck with the ill-fate which has often beset the dogs accompanying the explorers. Recently Baashuus-Jessen (1935) has carefully studied the accounts of many of these important expeditions and, according to this author, the lack of proper food containing right amounts of fat, minerals and vitamins was the principal cause of nervous diseases and malnutrition in the animals. In the Arctic and Antarctic regions, nevertheless, some most successful journeys have been accomplished with the aid of dogs. Unfortunately, it should be added that though the explorers reached their goals, it was often at the expense of their animals. Without doubt, also, when a stage is reached where dogs have to be sacrificed to feed the living, the latter are not in much better condition than those which were killed. Personally I should like to see or hear of an expedition, to one of the Poles or to some other place difficult of access, where all the dogs would return in good condition, to show the world what could be done with proper food and management. This article has been written for the Institute in the hope that the information about sledge-dogs may be of some assistance to those about to undertake expeditions in the Arctic regions. In this connection I should like to say that no other domesticated animal can withstand the hardships of the north better than the dog. He can follow man wherever he goes, and I have wondered why he is not more used, for instance, in mountaineering at the lower levels. The dog, being a native animal, winters well if he is properly fed, and should be at his best when the days begin to lengthen, which is just the time of year long journeys are undertaken. I will conclude by hoping that some of our young men will make a study of this matter: first of all by getting a thorough understanding of the mechanical laws involved in traction and harnessing; secondly, in working out balanced rations with the food available in the different countries where the dogs are to be ...